DESKRIPSI IMPLEMENTASI PEMBELAJARAN BERBASIS PROYEK TERHADAP PENGEMBANGAN LITERASI SAINS SISWA DI SDN WADAS IV KARAWANG - Anindyta, Minerva; Subeki, Ahmad; A’liyah, Umi Habibahtul; Ambar, Kurniasari (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
This research aims to describe, analyze the contribution, and identify the supporting and inhibiting factors in the implementation of the Project-Based Learning PjBL model in developing students' scientific literacy at SDN Wadas IV Karawang. This qualitative study, utilizing a case study method, involved one fifth-grade science teacher and ten students. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model. The findings indicate that the teacher successfully implemented the PjBL steps systematically. Students actively participated in scientific activities (such as project design and presentation), resulting in products like scientific posters and alternative energy models, which made learning more meaningful. The application of PjBL proved effective in enhancing students' scientific literacy, particularly in the aspects of knowledge, skills (critical thinking and collaboration), and scientific attitude. Although constraints such as limited time and facilities were identified, teacher support and student enthusiasm served as the key success factors. It is concluded that the PjBL model is effective in developing the scientific literacy of elementary school students and is relevant for application within the Merdeka Curriculum, as it promotes active, collaborative, and contextual learning. ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan, menganalisis kontribusi, serta mengidentifikasi faktor pendukung dan penghambat implementasi model Project-Based Learning (PjBL) dalam pengembangan literasi sains siswa di SDN Wadas IV Karawang. Penelitian kualitatif dengan metode studi kasus ini melibatkan satu guru IPA kelas V dan sepuluh siswa. Data diperoleh melalui observasi, wawancara, dan dokumentasi, dan dianalisis menggunakan model Miles dan Huberman. Hasil penelitian menunjukkan bahwa guru berhasil melaksanakan langkah-langkah PjBL secara sistematis. Siswa aktif berpartisipasi dalam kegiatan ilmiah (misalnya merancang proyek dan presentasi), menghasilkan produk seperti poster ilmiah dan model energi alternatif, yang membuat pembelajaran lebih bermakna. Penerapan PjBL terbukti efektif meningkatkan literasi sains siswa, terutama pada aspek pengetahuan, keterampilan (berpikir kritis dan bekerja sama), dan sikap ilmiah. Meskipun ditemukan kendala pada keterbatasan waktu dan fasilitas, dukungan guru dan antusiasme siswa menjadi faktor kunci keberhasilan. Disimpulkan bahwa model PjBL efektif dalam mengembangkan literasi sains siswa sekolah dasar dan relevan diterapkan dalam Kurikulum Merdeka karena mendorong pembelajaran aktif, kolaboratif, dan kontekstual.